A Markerless Augmented Reality Environment for Medical Data Visualization - Macedo, Márcio C. F.; Almeida, Caio S. de B.; Souza, Antonio C. S.; Silva, Josildo P.; Apolinário Jr., Antonio L.; Giraldi, Gilson A. (Anais do Simpósio Brasileiro de Computação Aplicada à Saúde (SBCAS); 2014: Anais do XIV Workshop de Informática Médica, 2014)
Augmented Reality (AR) techniques can be applied in medicine to help physicians in diagnosis, treatment planning, surgery simulation, among others. In craniofacial treatments, it can also be used to support prediction in patient’s own body. In this context, AR applications should fill more requirements than usual, like markerless support, tracking deformable objects and volume rendering. This paper presents a markerless AR environment, with support to deformable models, for volumetric medical data visualization based on a simple off-the-shelf hardware.